ANALISIS VEGETASI TUMBUHAN BAWAH PADA AREAL LAHAN BEKAS TAMBANG EMAS RAKYAT - Jeskiel Sipayung; Delvian Delvian; Kansih Sri Hartini (Peronema Forestry Science Journal, 2016)
The activity of mining has negative effects to the soil both physical, chemical, and biological. In Physically the structure of the soil, its texture, and porosity will be broken. Mine waste (Tailing) will influence in plant growth because the tailing contained mercury (Hg), lack of micro and macro nutrition and lack of organic substances. Reclamation activities are needed. As a starting point on reclamation, it is a need to be known what locally ground cover which can live in a mining field will be recommended to be planted. This research purposing on knowing what the type of ground cover vegetation which exist on field area of ex civillian gold mining in Kecamatan Naga Juang Kabupaten Mandailing Natal, knowing soil chemical condition for parameter pH, organic-C, available-P, KTK, choose cover vegetation potential for reclamation actifity. Vegetation data collection done in 20 m x 20 m plot purposively arranged, then the K (density), KR (relative density), F (frequency), FR (relative frequency), and INP (important value index) will be analyzed. Result of the research showing that there are 23 type of ground cover vegetation; Paspalum conjugatum, Micania micrantha, Acmella uliginosa, Paspalum comemersorili, Ageratum conyzoides, Crassocephalum crepidioides, Bidens sp, Sida rhombifolia, Solanum torvumn, Ipomea hederaceae, Diplazium esculentum, Calopogonium mucunoides, Borreria sp, Centrosema pubescens, Andropagu aciculatus, Borreria laevis, Amaranthus sp, Cucumis sp, Colocasia esculenta, Chrysopogon sp, Physalis anguleta, Urena lobata, Polygala paniculata. Condition for parameter pH: somewhat acid, organic-C: low, available-P: moderate, KTK: moderate. From those 23 type, there are 5 ground cover potential as pioneer plant based on the highest INP; Paspalum conjugatum (INP: 73,108), Micania micrantha (INP: 36,757), Acmella uliginosa (INP: 10, 968), Paspalum comemersorili (INP: 10,067), Ageratum conyzoides (INP: 9,016). Keywords: gold mining, field reclamation, ground cover